Guidelines for the Use of Cannabinoid Compounds in Chronic Pain - AJ Clark; ME Lynch; M Ware; P Beaulieu; IJ McGilveray; D Gourlay (Pain Research and Management)
OBJECTIVE: To provide clinicians with guidelines for the use of cannabinoid compounds in the treatment of chronic pain.